PENGARUH EKSTRAK DAUN LIDAH BUAYA (Aloe vera L.) TERHADAP PERTUMBUHAN JAMUR Candida albicans SECARA IN VITRO - Feizia Huslina (Universitas Islam Negeri Ar-Raniry, 2017)
The purpose of this study was to determine the ability of aloe vera leaf extract (Aloe vera L.) in inhibiting the growth of Candida albicans fungi through in vitro. Aloe vera (Aloe vera L.) is a plant that can overcome digestive problems caused by fungi. One of the pathogenic fungi causing gastrointestinal infections is C. albicans. This research was conducted in Microbiology Laboratory of FMIPAUnsyiah which lasted from April to May 2010. A Completely Randomized Design (RAL) consisted of 5 treatments and 5 replications is used in this study. The treatment was arranged on P0 = 20 Î¼l distilled water, P1 = aloe vera leaf extract concentration 100%, P2 = aloe leaf extract concentration of 50% and P3 = aloe leaf extract concentration of 25%. Aloe vera leaf extract (Aloe vera L.) was given to each treatment at 20 Î¼l. The parameter observed was the diameter of the inhibit zone formed. The data were analyzed using Variant Analysis (ANOVA), then continued with the Smallest Significant Difference (BNT) test. The results of this study indicated that the presence of aloe vera leaf extract (Aloe vera L.) could inhibit the growth of C. albicans. The higher the concentration of aloe vera leaf extract (Aloe vera L.), the higher the ability of it to inhibit C. albicans. The diameter of the inhibitory zone formed will enlarge along with the increasing of the concentration of aloe vera leaf extract (Aloe vera L.). The extract concentrations of 100%, 50% and 25% had their resistance capability of 0.50 mg, 0.24 mg and 0.20 mg of nistatin antibiotics.